Analisis Persepsi Konsumen dan Strategi Pemasaran Beras Analog (Analog rice) - Deviany Amanda Rizki; Jono M. Munandar; M. Syaefudin Andrianto (Jurnal Manajemen dan Organisasi, 2013)
Analog rice is artificial ricewhose material is not from paddy, but it is made from a variety of local flour (corn, sago and shorgum). As a new product, Rice Analog require appropriate marketing strategies through analysis of consumer perception. This research purposes are to develop a marketing strategy through identification Analog Rice segmentation, targeting and positioning based on consumer perception. The analytical method used were crosstabs analysis, cluster analysis and biplot analysis with 73 respondent. Crosstabs result indicated that consumer characteristics (age, marital status, education, income and expenses of month), associated with their impression and interested  to re-purchase. Cluster analysis was delivered into four market segments, the third target market are 31-40 years old, married, the level of income of IDR 4,500,001 to IDR 6,000,000. Biplot analysis deliver positioning for Analog Rice product therefore this rice offers “health benefits”, “nutritive ingredients”, and “safe to consumed”.Keywords : Analog rice, consumer perceptions, marketing strategy, cluster analysis, biplot analysis.